A functional analysis of Carabelli trait in Australian aboriginal dentition. Issue 2 (10th August 2020) - Fung, Sarah; Lee, Jinyoung; Yong, Robin; Ranjitkar, Sarbin; Kaidonis, John; Pilbrow, Varsha; Panagiotopoulou, Olga; Fiorenza, Luca
Abstract: Objectives: Carabelli is a nonmetric dental trait variably expressed as a small pit to a prominent cusp in the maxillary molars of modern humans. Investigations on the occurrence and expression rates of this trait have been conducted extensively, tracing its origin to genetic sources. However, there remains a lack of understanding about its potential role in chewing. In this study, we examine molar macrowear with the aim of reconstructing Carabelli trait occlusal dynamics occurring during chewing. Methods: We have examined 96 deciduous and permanent maxillary molars of children and young adults from Yuendumu, an Australian Aboriginal population that was at an early stage of transition from a nomadic and hunter‐gatherer way of life to a more settled existence. We apply a well‐established method, called Occlusal Fingerprint Analysis, which is a digital approach for analyzing dental macrowear allowing the reconstruction of jaw movements required to produce wear pattern specific to each tooth. Results: Carabelli trait slightly enlarges the surface functional area, especially in those molars where this feature is expressed in its cuspal form and it is closer to the occlusal plane. Moreover, the highly steep contact planes would also indicate that Carabelli wear areas contribute to increasing the shearing abilities of the occluded teeth, which are particularly important when processing fibrous and tough foods. Conclusions: The macrowear analysis suggests that Carabelli trait in the Aboriginal people from Yuendumu slightly enhanced occlusion and probably played some functional role during mastication. Future biomechanical and microwear analyses could provide additional information on the mechanical adaptation of Carabelli trait in modern human dentition.